The Usborne illustrated dictionary of science - Stockley, Corinne (Usborne London, 2012)
Provides a reference point for students studying for their SATs and GCSEs. This title is split into three sections, each covering the key aspects of the curriculum for Physics, Biology and Chemistry, and including important charts, tables and lists.